(untitled) (Raparin Journal of Humanities (RJH), 2025)
This study aims to measure and evaluate the level of quality of financial reporting in the Iraq Stock Exchange, as well as evaluate and analyze the value of the establishment of companies listed in the market and test the relationship and impact of the quality of financial reporting on the value of the enterprise. In order to achieve the objectives of the study, a main hypothesis was adopted directed to test the relationship between the two variables of the study within the framework of the practical side of the study, as the applied approach based on evaluation and quantitative mathematical analysis was adopted, as the annual financial statements of the companies listed on the Iraq Stock Exchange and the official bulletins of the market were adopted as data sources for the period (2017-2021). The sample of the study was mainly a sample of companies listed on the Iraq Stock Exchange, which amounted to (30) companies, and was selected in light of the sample of companies that do not apply the standards of (IFRS) and the sample of banks applying the standards of (IFRS) and the number (11) banks. The study reached a set of results, the most prominent of which is that there is no correlation and significant impact between the quality of financial reporting and the market value of enterprises applying and not applying IFRS standards Therefore, the study reached a set of conclusions, the most important of which was the need for the management of establishments to seek to identify other means that are positive indicators for investors and a source of their expectations when making their decisions related to the sale and purchase of shares, which is one of the means to raise the value of the facility.